Perovskite LaNiO3/Ag3PO4 heterojunction photocatalyst for the degradation of dyes - Ameen, Shahzad; Murtaza, Maida; Arshad, Muhammad; Alhodaib, Aiyeshah; Waseem, Amir (Frontiers in Chemistry, 2022)
Pristine lanthanum nickelate (LaNiO3), silver phosphate (Ag3PO4) and perovskite lanthanum nickelate silver phosphate composites (LaNiO3/Ag3PO4) were prepared using the facile hydrothermal method. Three composites were synthesized by varying the percentage of LaNiO3 in Ag3PO4. The physical properties of as-prepared samples were studied by powder X-ray diffraction (pXRD), Fourier-transform infrared (FT-IR), Scanning electron microscopy (SEM) and Energy-dispersive X-ray (EDX). Among all synthesized photocatalysts, 5%LaNiO3/Ag3PO4 composite has been proved to be an excellent visible light photocatalyst for the degradation of dyes i.e., rhodamine B (RhB) and methyl orange (MO). The photocatalytic activity and stability of Ag3PO4 were also enhanced by introducing LaNiO3 in Ag3PO4 heterojunction formation. Complete photodegradation of 50 mg/L of RhB and MO solutions using 25 mg of 5%LaNiO3/Ag3PO4 photocatalyst was observed in just 20 minutes. Photodegradation of RhB and MO using 5%LaNiO3/Ag3PO4 catalyst follows first-order kinetics with rate constants of 0.213 and 0.1804 min-1, respectively. Perovskite LaNiO3/Ag3PO4 photocatalyst showed the highest stability up to five cycles. The photodegradation mechanism suggests that the holes (h+) and superoxide anion radicals 〖(O〗_2^( •-)) plays a main role in the dye degradation of RhB and MO.